2012
DOI: 10.21236/ada590811
|View full text |Cite
|
Sign up to set email alerts
|

Root Causes of Nunn-McCurdy Breaches - A Survey of PARCA Root Causes Analyses, 2010-2011

Abstract: Cause Analyses. The views, opinions, and findings should not be construed as representing the official position of either the Department of Defense or the sponsoring organization. Acknowledgments Thank you to David L. McNicol, Caolionn L. O'Connell, and David A. Sparrow for performing technical review of this document.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The data are drawn fromDiehl et al (2012), which provides a synthesis of the results of the 15 root cause analyses (RCAs) undertaken by RAND or IDA, as required by the Weapon Systems Acquisition Reform Act of 2009. (The RAND studies are reported inBlickstein et al [2011Blickstein et al [ , 2012;Diehl et al [2012] provide the references to the individual IDA studies.) Only 12 data points appear in Figure2because three of the 15 programs for which RCAs were done were major automated 11 Defense ARJ, January 2022, Vol.…”
mentioning
confidence: 99%
“…The data are drawn fromDiehl et al (2012), which provides a synthesis of the results of the 15 root cause analyses (RCAs) undertaken by RAND or IDA, as required by the Weapon Systems Acquisition Reform Act of 2009. (The RAND studies are reported inBlickstein et al [2011Blickstein et al [ , 2012;Diehl et al [2012] provide the references to the individual IDA studies.) Only 12 data points appear in Figure2because three of the 15 programs for which RCAs were done were major automated 11 Defense ARJ, January 2022, Vol.…”
mentioning
confidence: 99%